Nutritional Intake, Body Mass Index, and Activity in Postacute Traumatic Brain Injury: A Preliminary Study. Issue 3 (17th January 2014) - Duraski, Sylvia A.; Lovell, Linda; Roth, Elliot J.
Abstract Purpose In the United States, traumatic brain injury (TBI) remains a serious health problem contributing to lifelong disability. Little has been written about nutrition problems experienced postrehabilitation discharge. Our objective was to describe the nutrition and weight management characteristics of TBI survivors after discharge from rehabilitation and to identify characteristics of individuals at risk for weight control issues. Method/Design Twenty‐six TBI survivors admitted to a freestanding rehabilitation hospital were followed for 1 year postdischarge. Data on height, weight, disability rating, diet and activity were collected at admission, 3, 6, 9 and 12 months after discharge. Findings Approximately 30% of the participants showed an increasing body mass index from discharge to 1‐year follow up. Two patients had more complete long‐term data and are highlighted. Conclusion/Clinical Relevance The case studies provide insight into the need for rehabilitation nurses to provide nutrition education to TBI survivors that will accommodate changes in lifestyle and activity after discharge.